Mouse Cookies 10 Easy-to-Make Cookie Recipes with a Story in Pictures - Laura Numeroff; Felicia Bond (U.S.A Scholastic Inc., 1995)
From School Library Journal Grade 2-4?Some cookbooks related to children's stories strain for relevance, but this one is a funny, imaginative extension of Numeroff's much-loved If You Give a Mouse a Cookie (HarperCollins, 1985). The story in this spiral-bound book has no words: it is told through Bond's droll, detailed watercolors on the pages facing 10 recipes. It takes place in the mouse's house in the base of a large tree trunk, where he is baking. The boy from the previous book, still wearing the same gold shirt trimmed in green, is peeking through the tiny window and watching the cheerfully messy procedure. The rodent is so weary by the time the first batch is in the oven that he takes a nap and the cookies burn. The rest are fine, though?and before he eats them all himself, he hands one out the window to the boy. Most of these good-old favorite cookies are made from scratch, and the directions are clear. Just the thing for mice and boys and the rest of us? Carolyn Jenks, First Parish Unitarian Church, Portland, ME Copyright 1995 Reed Business Information, Inc.
Keywords: Cooking Book -- Cooking Book